Experimental approaches for the diagnostics of hydroacoustic problems in naval propulsion. (15th September 2015) - Felli, M.; Falchi, M.; Dubbioso, G.
Abstract: Current standard experimental methodologies in hydro-acoustics rely on far-field measurements that enable the characterization of the spectral properties and the determination of the sound pressure level with good precision but fail in identifying accurately the flow phenomena at the origin of sound generation and radiation. The present paper reviews two "unconventional" approaches to address the diagnostics, analysis and solution of hydroacoustic problems in naval engineering experimentally. The first approach, based on direct pressure fluctuation measurements combined with detailed flow measurements in the proximity of the noise source, provides a direct estimate of the flow phenomena at the origin of sound generation and emission. The second approach is a relatively recent strategy to investigate the sources of acoustic noise in the aeronautical field and concerns the use of volumetric techniques, such as Tomographic PIV (Elsinga et al., 2006 ), in combination with acoustic analogies. The abilities of the two approaches are investigated with reference to the analysis of the noise sources in some case studies consisting of an isolated propeller, a propeller operating in the wake a surface ship, and an open-water propeller-rudder system. Both approaches are shown to enable the physical interpretation of the potential mechanisms of noise generation and emission from a naval propeller. For example: (i) the combined employment of Tomographic PIV measurements with the Powell׳s acoustic analogy proved the dominant contribution of the tip vortices to the radiated far-field noise in non-cavitating conditions and showed the different directivity of the quadrupoles associated with the tip vortex, the trailing wake and the hub vortex perturbation; (ii) the use of simultaneous near- and far-field measurements combined with cross-correlation techniques revealed the direct relationship between the acoustic perturbation and the Azimuthal gradients of the blade hydrodynamic loads for an installed propeller in non-cavitating conditions; (iii) the application of a filtering procedure to separate the sound and pseudo-sound contributions from recorded near-field pressure fluctuation signals highlighted the different mechanisms underlying the acoustic and hydrodynamic perturbation in a propeller-rudder system. Highlights: Unconventional approaches for the diagnostics of hydro-acoustic problems. Application to three reference case studies of naval propulsion. First example of Tomographic PIV measurements applied to naval propulsion. Advanced signal acquisition and filtering methodologies are documented.